Med-X - Xu, Lisa X.; Li, Song.; Tong, Shanbao; Fowlkes, Brian; Ye, Jian.; Chen, Jun.; Cheng, Cheng-Kung.; Di Carlo, Dino.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Aim Med-X is a high-quality open-access journal that publishes breakthrough papers across the areas of Biomedical Engineering. The journal aims to provide an international and interdisciplinary platform for communicating the latest important discoveries and innovations in basic and applied biomedical sciences and technologies, through publishing state-of-the-art research articles, rapid communications, case reports, reviews, perspectives and commentaries. Scope Med-X covers the advances of basic and applied research in the field that integrates multidisciplinary approaches in life science, medical science, material science, chemistry and chemical engineering, mechanical engineering, electrical engineering, mathematics, and computer science and engineering to address challenges in medicine and health care. Med-X encompasses broad bioengineering and biotechnology topics at the frontiers of diagnosis, monitoring, treatment, and prevention of human diseases for improving human health and well-being. Topics covered in Med-X include but not limited to the followings: 1. Molecular and Cellular Engineering; 2. Smart Biomaterials and Tissue Engineering; 3. Drug, Gene and Cell Delivery Systems; 4. Immunoengineering; 5. Biomechanics and Mechanobiology; 6. Biothermal Science and Engineering; 7. Biomedical Devices and Biosensors; 8. Medical Robotics, Artificial Intelligence, and Telemedicine 9. Biomedical Imaging; 10. Bioinformatics and Computational Biology; .
Keywords: Medicine$1 (BResearch.s; Biology$1 (BResearch.s; Regenerative medicine; Biomedical engineering; Biomaterials; Biomechanics; Bioinformatics; Biomedical Research; Regenerative Medicine and Tissue Engineering; Biomedical Engineering and Bioengineering; Biomaterials; Biomechanics; Computational and Systems Biology